Justice Holmes’s Response to Legal Formalism in Context: A View on the Cornerstone of a Realistic Approach to the Common Law (Italian Review of Legal History, 2024)
A realistic approach to common law is one of the most authoritative views on the role and potential of judges in law-making. American judge Oliver Wendell Holmes, Jr. was a mastermind of legal realism and held a very special position among his fellows. Conventionally, legal realism is considered a progressive and innovative movement of the late XIX and the first half of the XX centuries. However, as this study demonstrates in several respects, some of its proponents can be labelled conservatives who defended their view of the traditional approach of judge-made law. Realists inspired by Holmes countered the formalist trends within common law, which was initially and historically alien to them (e.g. Langdellism). The formalist methodology and its results were often reminiscent of the Reception of Roman Law, which ancient common law rejected. Not surprisingly, it was highly criticized as an imposition of artificially invented legal ideals on a particular society regardless of its real-life experience. Based on Holmes’s original writings and their credible interpretations, this survey aims to explore his anti-formalist approach within a broader context of its theoretical origins. It reveals the historical and legal roots of the ‘realism formalism’ antagonism in the common law, reflecting, as a result, the global contrast of two civilizational approaches to legal epistemology (common law v. civil law). Case-based conceptual legal thinking typical for common law is considered through the lens of Holmes’s findings on the process of gradual formation of legal principles. Realistic aspiration to ensure that law reflects the actual demands of the community is explained as a claim for real democracy as opposed to the formal one. A refreshing contextual view of Holmes’s teachings may unfold for a continental reader the possibility of treating the modern concept of deliberative democracy and models of constitutional interpretation, such as the living constitution or popular constitutionalism, from the perspective of a realistic approach.
Keywords: Oliver Wendell Holmes, Jr.; common law; general theory of law